Inclusive Growth and Sustainable Human Development in Nigeria - Campbell, Omolara A (Advances in Social Sciences Research Journal, 2017)
Previous studies have confirmed the position that higher education is a sine-qua-non for human capital development and economic growth. The 2014 rebasing of Gross Domestic Product made Nigeria the 26th largest economy in the world and the biggest in Africa. Recently, the International Monetary Fund (IMF) pronounced Nigeria again as having the largest economy in Africa. Yet Africa’s largest economy faces a myriad of challenges, such as high prevalence of poverty, unemployment, underemployment, youth unemployment, huge infrastructure deficits, income and social inequalities. However, the Sustainable Development Goals (SDGs) has its goal 8 as “promoting sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all” by 2030. Based on this background, this paper proceeds to examine how human development can translate to inclusive economic growth. It focuses mainly on enhancement of human capabilities which is one of the key drivers of inclusive growth. It assesses the status and performance of the indicators of human development in Nigeria and compares the outcomes with that of the emerging and developed nations. Utilizing secondary data and descriptive statistical analytical tools, the paper finds out that the indices of human development and the knowledge economy recorded higher values in the emerging and developed countries than what exists in the developing countries. The paper therefore recommends the urgent need for policy makers to formulate appropriate policy mix that will ensure increase in investment in human capital and all indices of human development and knowledge economy. This is expected to be via improvement in quantity and quality of education in general and higher education in particular for individuals to contribute to and benefit from economic growth. Key Words: Human Development, Human Development Indices, Inclusive Growth and Knowledge Economy Indices.